The Montessori Method as A Pedagogical Strategy to Support Children's Self-Regulation in Early Childhood Education: A Systematic Literature Review - Lisna Jelita; Enindya Zen Akalili; Dinar Intan Fadilah; Faiz Fatihul Alwan (Educational Psychology Journal, 2025)
This study aims to examine the relationship between the Montessori method and self-regulation skills in early childhood through a Systematic Literature Review (SLR) approach. Self-regulation is an important foundation for children's psychosocial development and long-term academic success. The Montessori method, which emphasizes independence, freedom within limits, and a structured environment, is considered to have the potential to support the development of this aspect. The identification process involved 17 scientific articles published between 2015 and 2025. Inclusion criteria included empirical studies (quantitative and qualitative), a focus on early childhood, and a direct link between the Montessori approach and self-regulation. Data were collected through Google Scholar, with additional searches conducted on ScienceDirect, DergiPark, and ResearchGate to broaden the scope of relevant studies. The synthesis of findings showed that the majority of studies reported a positive relationship between Montessori implementation and improved self-regulation in children, particularly in the cognitive (executive function and attentional control) and behavioral (independence and self-discipline) dimensions. Evidence also supports a positive influence on emotional regulation, although the number of studies on this aspect remains limited. Variations in results are largely due to differences in study design, intervention duration, and implementation context. This SLR concludes that the Montessori method is an effective pedagogical approach in supporting the holistic development of self-regulation in early childhood. These findings have important implications for educators, parents, and early childhood curriculum designers to consider Montessori principles in efforts to strengthen children's self-regulation capacities from an early age. Keywords: Self-regulation, Montessori Method, Early Childhood, Pedagogical Strategies.